Triple Hurdle Model with Zero Expenditures - Chi, Yeong Nain (Quarterly Journal of Econometrics Research, 2018)
The Tobit model is a one-step decision method, implying that the decision to participate and the decision of how much to spend are influenced by the same variables and in the same manner. The double hurdle model is a two-step decision process; consumers first decide whether or not to participate, and then a second decision is made on how much to spend. The triple hurdle model has three separate stochastic decision choices for the first stage of awareness, the second stage of participation, and a final stage of consumption decision. This study provides a guidance in the choice of an appropriate model, which all observations can be used in the estimation for awareness and participation decisions, but only positive observations that pass awareness, participation and consumption decisions simultaneously can be used in the estimation based on a censored and truncated sample, allowing for richer interpretation of consumer choice behavior.